PSYCHOLOGICAL METHODS OF DEVELOPING PERSONNEL MANAGEMENT SYSTEMS IN INDUSTRIAL ENTERPRISES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
To date, HR management has become a hot topic for most research. HR-management currently plays a key role in the economic development of the country